Assessment of Memory Impairment in Early Diagnosis of Alzheimer's Disease - Vyhnálek, Martin; Marková, Hana; Laczó, Jan; De Beni, Rossana; Di Nuovo, Santo (Current Alzheimer research, 2019)
Memory impairment has been considered as one of the earliest clinical hallmarks of Alzheimer's disease. This paper summarizes recent progress in the assessment of memory impairment in predementia stages. New promising approaches of memory assessment include evaluation of longitudinal cognitive changes, assessment of long-term memory loss, evaluation of subjective cognitive concerns and testing of other memory modalities, such as spatial memory. In addition, we describe new challenging memory tests based on memory binding paradigms that have been recently developed and are currently being validated.
Keywords: Female; Memory Disorders; spatial memory; ženské pohlaví; lidé; poruchy paměti; subjective cognitive decline.; časná diagnóza; neuropsychological assessment; Alzheimer's disease; Male; Aged; Alzheimer Disease; mild cognitive impairment; Elderly; Early Diagnosis; Alzheimerova nemoc; memory impairment; senioři; mužské pohlaví; memory binding; Humans